Perancangan Mesin Pelontar Bola Tennis Berbasis Remote Control - Abdul Tahir; Musakirawati Musakirawati (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
All of tennis athletes can play tennis properly because they practice for hours, months and even years. There are many ways that can be done to practice playing tennis, namely by using a wall or with the help of a ball throwing machine. Several tennis ball throwing machines developed by researchers have been found, although they are not optimal. Basically, the principle of throwing a tennis ball is almost the same as throwing a table tennis ball, namely using an electric motor as a trigger for the throwing motion. For reference and source of knowledge, the researchers conducted a perc ejection machine by combining a machine with a joystick-based remote control using an Arduino type microcontroller, an electric motor type driving motor. With this combination the machine can be adjusted for vertical and horizontal movement and can adjust the speed of the ejector by programming on the side of the microcontroller. The results of the design are drawings of arrangement, drawings of parts, sizes and materials used and drawings of a three-dimensional machine with a size of 100 cm x 70 cm x 140 cm.